The Geopolitical Laplander: From Olaus Magnus to Johannes Schefferus - Balzamo, Elena (Umeå University Library, 2014)
After being either completely ignored or mixed up with monsters and devils, which in the medieval imagination dwelled in the Extreme North, the Sami were suddenly brought into the limelight by Olaus Magnus (1492–1557), Swedish catholic bishop in exile. His Carta marina (1539) and Historia de gentibus septentrionalibus (1555) contain most valuable information, depicting the Sami’s natural virtues, practical skills and mysterious magic powers. The image provided by these works became widely spread in Europe thanks both to the reprints of the Latin originals and to the numerous translations. In the seventeenth century the theme was re-actualized by a new publication, entirely devoted to Lapland and its inhabitants: Lapponia (1673) by Johannes Schefferus (1621–1679). Translated into a number of languages it replaced the image created by Olaus Magnus with a new one, at the same time similar and different. The present paper examines some crucial points of this evolution in order to show that both “portraits” reflect motivations that go beyond purely scholarly interest: each of them is part of the ideological struggle of its time—the Reformation in one case, the conflicts brought to life by the Thirty Years’ War in the other.